TRANSLATION IDEOLOGY ON VOCATIVE VERBAL EXCHANGES IN PHILLIP PULLMAN’S NOVEL - Sipayung, Kammer Tuahman; Wafa, Ali (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
Translation’s core ideology lies in guiding translators' decision-making processes, particularly concerning the social and cultural aspects of source and target texts. This study employed a descriptive qualitative approach. It delved into the translators’ ideological stance in rendering an English novel into Indonesian, focusing on vocative verbal exchanges. The analysis employed Miles and Huberman's interactive data analysis techniques (2014), incorporated Molina and Albir's translation procedures (2002), as well as Newmark's methods (1988). Venuti's theory (2003) was utilized to unveil the translator's ideology. Findings reveal that the translator is inclined towards foreignization at the word and phrase levels. This was juxtaposed with a preference for domestication at the clause and sentence levels. This suggests a nuanced approach, where the translator aimed to preserve the source text's essence in smaller linguistic units while enhancing readability in larger units for the target audience. In essence, the translator strategically positions themselves between the source and target languages, neither leaning too closely towards one nor the other, striving for a neutral stance that upholds the original message while ensuring accessibility for the target readers.